The limited impact of adverse experiences on worldviews and ideologies - Vilanova, Felipe; Almeida-Segundo, Damiao Soares; Moura, Pablo Borges; Pratto, Felicia; Costa, Angelo Brandelli (Frontiers in Social Psychology, 2024)
The impact of adverse experiences on clinical symptoms has been consistently demonstrated, but their impact on ideologies and worldviews has been rarely tested empirically. It has been long assumed that threatening experiences increase Dangerous World Beliefs (DWB) and Right-Wing Authoritarianism (RWA), whereas scarcity experiences increase Competitive World Beliefs (CWB) and Social Dominance Orientation (SDO). Here we assess whether self-reports of these adverse experiences are associated with clinical symptoms, worldviews and ideologies across two distinct studies (Ntotal = 1,108). Study 1 comprised Brazilian youth and results indicated that adverse experiences are consistently associated with depression, anxiety and stress but only marginally associated with DWB, RWA, CWB and SDO. Study 2 comprised male prisoners with higher degree of adverse experiences and similar results were observed, as adverse experiences were mostly unrelated to worldviews and ideologies. Comprehensively, this research challenges the theoretical foundations of worldviews and ideological development, posing questions to the existing models and advocating for new frameworks that promote a shift from models grounded in clinical assumptions to frameworks focusing on social influences.